2020
DOI: 10.1096/fj.202000954r
|View full text |Cite
|
Sign up to set email alerts
|

AMPK mediates energetic stress‐induced liver GDF15

Abstract: Growth differentiating factor‐15 (GDF15) is an emerging target for the treatment of obesity and metabolic disease partly due to its ability to suppress food intake. GDF15 expression and secretion are thought to be regulated by a cellular integrated stress response, which involves endoplasmic reticulum (ER) stress. AMPK is another cellular stress sensor, but the relationship between AMPK, ER stress, and GDF15 has not been assessed in vivo. Wildtype (WT), AMPK β1 deficient (AMPKβ1−/−), and CHOP−/− mice were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 66 publications
(171 reference statements)
0
14
0
Order By: Relevance
“…In mouse models of ischaemia–reperfusion injury, GDF15 deficiency correlated with a major damage and cardiomyocyte apoptosis, while treatment with GDF15 counteracts ischaemia–reperfusion injury ( 177 179 ). This positive action of GDF15 treatment in obese and in ischemia-reperfused mice suggest that high levels of GDF15 play a compensatory role as recently suggested by Townsend et al., who demonstrated that the increase in hepatic GDF15 is associated with the energy stress response controlled by AMPK ( 180 ). Additionally, Patel et al.…”
Section: The Circadian System: An Orchestra Of Signals Synchronizes F...mentioning
confidence: 54%
“…In mouse models of ischaemia–reperfusion injury, GDF15 deficiency correlated with a major damage and cardiomyocyte apoptosis, while treatment with GDF15 counteracts ischaemia–reperfusion injury ( 177 179 ). This positive action of GDF15 treatment in obese and in ischemia-reperfused mice suggest that high levels of GDF15 play a compensatory role as recently suggested by Townsend et al., who demonstrated that the increase in hepatic GDF15 is associated with the energy stress response controlled by AMPK ( 180 ). Additionally, Patel et al.…”
Section: The Circadian System: An Orchestra Of Signals Synchronizes F...mentioning
confidence: 54%
“…Also reported is the pathophysiological function of GDF15 in regulating ER stress. Through UPR signaling, ER stress promotes GDF15 expression and release [59]. Moreover, ablation of GDF15 lowers ER stress-induced β-cell apoptosis in diabetes [60].…”
Section: Discussionmentioning
confidence: 99%
“…Although GDF-15 is expressed in various tissues, its role as an adipokine that regulates metabolism, which overlaps with the functions of adiponectin, has attracted increasing attention. In addition, GDF-15 and adiponectin can improve IR via the activation of adenosine monophosphate-activated protein kinase (AMPK), a cellular energy sensor, in the liver and skeletal muscles, respectively ( 37 , 38 ). The G/A ratio is a recently proposed index whose increment was independently correlated with the risk of T2DM in all study populations aged 18–70 years and subgroups, compared to GDF-15 or adiponectin levels alone after adjusting for confounders; however, adiponectin concentrations had a stronger association with T2DM in relatively healthy men, but not in relatively healthy women and participants with metabolic disorders ( 17 ).…”
Section: Discussionmentioning
confidence: 99%